PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA KELAS V SD - Rotua Batubara; Patri Janson Silaban; Anton Sitepu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research utilized a descriptive-analytical method and involved all grade VB students in the even semester at SD Negeri 067245 Bunga Asoka for the academic year 2020/2021, totaling 29 students. To determine students' initial abilities, a Pre-Test was conducted with an average score of 63.72, indicating sufficient initial skills. The Post-Test results increased to 80.55, showing an improvement in students’ critical thinking skills. The correlation coefficient indicated a significant effect of the Problem-Based Learning model (X) on critical thinking skills (Y), with rcount > rtable (0.852 > 0.367). Hypothesis testing using the t-test also showed tcount > ttable (8.478 > 1.703) at a significance level of α = 0.05, confirming the effectiveness of the model. Based on these results, the Problem-Based Learning model was considered very effective in enhancing thematic learning and improving critical thinking skills in the classroom.